Ageing of climbing ropes with and without hydrophobic coating - Sedlácek, D.; Roso, M.; Viel, L.; Perotto, N.; Caven, B.; Hasler, M.; Nachbauer, W. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
The effects of 4 months of weather exposure on the ageing of dynamic climbing ropes made of polyamide 6 were studied and differences between ropes with and without hydrophobic coating were examined. The polyamide degradation of the rope yarns was studied using infrared spectroscopy and a quasi-static tensile test. The number of falls to failure and the maximum force on the climber in a fall were evaluated with a drop test according to the UIAA 101 standard. Moreover, changes in the length of the ropes due to weathering were measured. The following results were found. After 4 months of weathering, sheath yarns of the coated rope showed a greater decrease in breaking force than those of the uncoated rope, which might be due to reactions of polyamide with radicals formed during the photo-induced oxidation of the coating. In contrast, the core yarns from the uncoated rope showed a greater decrease in breaking force than those from the coated rope, probably due to prolonged exposure of the uncoated core to water with possibly dissolved atmospheric acids. Furthermore, the decrease in the number of falls to failure was greater in the uncoated than in the coated rope. This difference was explained by a mechanism of changes in radial pressure of the sheath on the core. Regarding the maximum force on the climber, no significant changes due to ageing were observed during the drop test. Thus, it was concluded that 4 months of weather exposure do not pose a safety risk for climbing ropes, but the negative effect of coating on the ageing of polyamide might be detrimental when it comes to static personal safety equipment, such as slings or accessory cords.